2019
DOI: 10.1002/cncr.32329
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative PET/CT does not accurately detect extrauterine disease in patients with newly diagnosed high‐risk endometrial cancer: A prospective study

Abstract: BACKGROUND:The identification of extrauterine disease is critical to the management of patients with high-risk endometrial cancer.The purpose of the current study was to determine the accuracy of preoperative positron emission tomography (PET)/computed to mography (CT) in the detection of extrauterine disease. METHODS: Women with high-risk endometrial cancer were enrolled prospectively and underwent preoperative PET/CT followed by surgery, including sentinel lymph node biopsy and lymphadenectomy. Primary tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…13,14,[27][28][29] Positron emission tomography / computed tomography (PET/CT) did not reliably predict the high-risk EC for high false-negative rates. 30 However, the radiomics developed in this study might be helpful in identifying the risk factors of EC preoperatively, being consistent with preliminary studies using MRI-based texture analysis of small sample size. 31,32 In the optimization process of the LASSO method for radiomics feature selection, the T 2 WI features had the highest weight in the radiomics signature, suggesting an important role of conventional sequence-based features in a prediction model.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…13,14,[27][28][29] Positron emission tomography / computed tomography (PET/CT) did not reliably predict the high-risk EC for high false-negative rates. 30 However, the radiomics developed in this study might be helpful in identifying the risk factors of EC preoperatively, being consistent with preliminary studies using MRI-based texture analysis of small sample size. 31,32 In the optimization process of the LASSO method for radiomics feature selection, the T 2 WI features had the highest weight in the radiomics signature, suggesting an important role of conventional sequence-based features in a prediction model.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies indicated a low specificity and accuracy of routine MRI in evaluating these risk factors 13,14,27–29 . Positron emission tomography / computed tomography (PET/CT) did not reliably predict the high‐risk EC for high false‐negative rates 30 . However, the radiomics developed in this study might be helpful in identifying the risk factors of EC preoperatively, being consistent with preliminary studies using MRI‐based texture analysis of small sample size 31,32 …”
Section: Discussionsupporting
confidence: 74%
“…In this study, PET was also significantly better than MR in the diagnosis of lymph nodes. But we found a large number of PET false-negative cases, which accords with the findings of endometrial cancer and non-small cell lung cancer studies [36,37]. Identifying PET false-negative cases has always been a clinical challenge.…”
Section: Discussionsupporting
confidence: 87%
“…In the literature, the relationship between the SUV max values of the primary tumor and presence of LNM is unclear. Husby et al ( 11 ) detected a considerable difference between the SUV max values of these two groups, whereas Stewart et al ( 12 ) found no differences in primary tumor characteristics on PET/CT imaging between patients with positive and negative lymph nodes.…”
Section: Discussionmentioning
confidence: 99%